Numerical Methods Using Java - For Data Science, Analysis, and Engineering - Li, Haksun (Apress, an imprint of Springer Nature, 2022)
Implement numerical algorithms in Java using NM Dev, an object-oriented and high-performance programming library for mathematics. You'll see how it can help you easily create a solution for your complex engineering problem by quickly putting together classes. This book covers a wide range of topics, including chapters on linear algebra, root finding, curve fitting, differentiation and integration, solving differential equations, random numbers and simulation, a whole suite of unconstrained and constrained optimization algorithms, statistics, regression and time series analysis. The mathematical concepts behind the algorithms are clearly explained, with plenty of code examples and illustrations to help even beginners get started.